The development of public administration from a global perspective: the case of Italy - Seguiti, Maria Laura (1999)
What is the impact of globalization on the Italian state and the development of the Italian public administration? Italy is one of those countries where the forces of globalization are challenging the strong state tradition and the predominance of the legal model of public administration. Globalization and the European regional integration push toward a diminished role of the state and a managerial public administration with an increased emphasis on efficiency and better quality of government activities. - Reproduced
Keywords: Globalization - Italy; Public administration - Italy; Public administration